Pemetaan Kemasaman Tanah Berdasarkan Tiga Tipe Penggunaan Lahan Di Desa Kawat Kecamatan Tayan Hilir Kabupaten Sanggau - Almaredha, Lea Holydelega; krisnohadi, Ari; Yulies V.I., Urai Suci (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2024)
Kawat village is located in Tayan Hilir District, Sanggau Regency, the area of the research site is 218.93 hectares or 9.67% of the total area of the Kawat village. The purpose of this study was to identify soil characteristics related to soil acidity, mapping soil acidity in Kawat Village, and provide liming recommendations at the research site. The data collection method was carried out by land surveying, namely a physiographic system where each observation point represented one land unit, there were eight observation points for the number of existing land units. Soil observations are carried out by: (a) making a soil profile, (b) digging minipit holes, and (c) soil drilling. Intact soil samples were taken using a ring sample and disturbed soil samples were taken using a ±1 kg hoe. Soil pH mapping was carried out using the kriging method The results showed that the soil pH at the study site ranged from 3.39 to 4.45. The results of the Ca2+analysis ranged from 0.55 to 2.44 (cmol(+)kg-1), and the results of the Mg2+analysis ranged from 0.20 to 1.00 (cmol(+)kg-1). The results of the K+ analysis ranged from 0.03 "“ 0.19 (cmol(+)kg-1), and the results of the Na+  analysis ranged from 0.03 "“ 0.30 (cmol(+)kg-1). At the research site, no sulfidic material was found. The C-organic content ranges from 0.50% to 57.02%. The results of the CEC (Cation Exchange Capacity) analysis at the study site ranged from 2.74 to 118.38 (cmol(+)kg-1). The results of the BE (Base Saturation) ranged from 2.41 to 29.76%. The results of the analysis of soil Al saturation ranged from 17,10 to 35,48%. The results of Fe analysis ranged from 19.14 to 92.35 ppm.The results of the soil texture analysis consist of dusty clay loam, clay, dusty clay, and dust. The depth of the groundwater table ranges from 6 - 120 cm. The results of the bulk density analysis ranged from 0.16 to 1.26 g/cm ³. The results of observations of soil structure consisted of crumbs, rounded lumps, angular lumps, and massive. The recommended liming ranges from 0.83 "“ 3.85 tons/ha of dolomite